Engineering characteristics of Avlamè lateritic aggregate for it use in road construction in the Republic of Benin - HOUANOU, KOCOUVI AGAPI; DOKO, KOUANDETÉ VALERY; Dossou, Kpomagbé Serge; PRODJINONTO, Vincent; Olodo, E.T. Emmanuel (My University, 2022)
Laterite aggregate is the most widely used material in road construction. In central Benin, laterites aggregates are available in quantity, especially in the Abomey plateau. Thus, the present study is initiated to characterize the laterite aggregate of Avlamè, a locality of the Abomey plateau, for use in road construction. To achieve this, an experimental study based on normative tests was used. The identification tests on the laterite aggregate of Avlamè made it possible to determine the rate of particles with a diameter lower than 80 mm, or 27.77%, the liquidity limit which is 35%, the plasticity index whose value is 17.67%, then the organic matter content equal to 0.03%. Similarly, the mechanical tests carried out resulted in the determination of the CBR index (California Bearing Ratio) evaluated at 58.00% for 95% OPM (modified proctor optimum), then the secant modulus whose value estimated at 360 days is 331.71±0.09 MPa. Determination of the secant modulus of the lateritic gravel makes it possible to evaluate the real deformation. Finally, these studies have shown that its mechanical parameters increase linearly with the maturation time of the specimens analysed. All in all, the analysis of the various results in accordance with the specifications of the CEBTP (Centre of expertise for building and public works) 1984 guide revised in 2019 shows that Avlamè's laterite aggregate can only be used as a sub-base, whatever the type of pavement.
Keywords: Laterite aggregate; Secant modulus; Avlamè quarry; Physical and mechanical properties; Pavement layers.